PENGARUH MINAT BELAJAR DAN METODE PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI DI SMA NEGERI 1 GARUT - Tri Setia Novianti, - (2007)
This research aim to know of influence of enthusiasm learn and study method to achievement learn student at accountancy subject. This research is conducted at class student of XI maiors of IPS in SMA Negež•i I Garut Method the used is verifikaúf. so that in this research of information collected from responder bv using questioner then analyzed by using calculation of this statistic. This research represent research of sample with amount of used sample that is 53 people from amount of population counted 113 people. Before doing data processing, witer use MSI (Interval successive methods) to change data from ordinal scale to interval scale. Variables which test in this research that is enthusiasm learn as first independent variable (Xi), method as a second independent variables (X2), and iearn achievement of student as variable of dependence (Y). Became in this research there are doubled independent variable. So that to know level of influence variable X of variable Y require to be done by calculation of statistic bv partial and simultaneous. From result of research got the level of correlation coefficient between Xl with Y by partial that is equal to 0,3928 with coefficient of determination equal to 15%. This matter show that the partial enthusiasm learn to have an effect on to achievement learn equal to 15%. Correlation coefficient between X2 with Y by partial that is equal to 0,4685 with coefficient of determination equal to 22%. This matter show that the partial study method have an effect on to achievement learn equal to 22%. While level of double correlation coefficient between and x l, X2 of Y that is equal to 0,628 with coefficient of determination 39,4%, which meaning that by simultaneous enthusiasm learn and study method have an effect on to achievement learn equal to 39.4%. Passing calculation test of for the variable Xl obtained by equal to 3,020, for variable of X2 obtained by tcount equal to 3,750 and equal tol ,676, so that tcount > table. While from calculation of test of F obtained by Fcount equal to 16,240 and 3,18 ( F count > Ftable). There by, hypothesis which raised in this research can be accepted that is: enthusiasm learn and study method by partial and simultaneous have an effect on positive to achievement learn student at accountancy subject.